Legal Vacuum in Indonesian Administrative Law: Urgency of Policy Regulation: Kekosongan Hukum dalam Hukum Administrasi Indonesia: Urgensi Peraturan Kebijakan - Putra, Eduard Awang Maha; Wibowo, Gatot Dwi Hendro; Minollah, Minollah (Indonesian Journal of Law and Economics Review, 2024)
This study delves into the critical need for explicit policy regulation within the Indonesian Government Administration Law (Law Number 30 of 2014), addressing a significant legal vacuum. Despite the law encompassing regulations related to discretion, it notably lacks specific terms or phrases for 'beleidsregel' (policy regulations), leading to legal uncertainties. Employing a normative legal research methodology, the research utilizes statutory and conceptual approaches to explore the interplay between the principle of discretion (freies ermessen) and policy regulations in the context of state administrative law. The findings reveal that while the principle of discretion and policy regulations are distinct entities, they are inextricably linked. The principle of discretion provides the foundational authority for state administrative officials to establish policies, whereas policy regulations represent the formal embodiment of these policies. The absence of beleidsregel in the current legislation leads to reliance on expert opinions (doctrine) and varying legal interpretations, fostering legal uncertainty (rechtsonzekerheid) and potential chaos (rechtsverwarring) in government administration. The study highlights the urgent need to regulate policy regulations within the Government Administration Law to ensure legal certainty and prevent administrative chaos, emphasizing the importance of formal legal frameworks in guiding and controlling the application of policy regulations by state officials. This research underscores the necessity of legislative reform to address the existing normative vacuum and stabilize the legal environment for effective governance in Indonesia.Highlights: The study emphasizes the lack of specific policy regulation terms in Indonesian Government Administration Law, leading to a legal vacuum. It highlights the crucial link between the discretion principle and policy regulations, underscoring their interdependence in state administrative law. The research identifies the urgent need for legislative reform to provide legal certainty and prevent administrative chaos due to the current absence of policy regulation guidance. Keywords: Policy Regulations, Legal Vacuum, Indonesian Administrative Law, Discretion Principle, Government Administration